Some of the applications level of the protection and control of mastitis in dairy cattle farms in turkey with different qualifications - Rişvanli, Ali; Saat, Nevzat; Şafak, Tarik; Yilmaz, Öznur; Yüksel, Burak Fatih; Kilinç, Mehmet Akif; Şeker, Ibrahim (Selcuk Universitesi, Veteriner Fakultesi, 2021)
Aim: In this study aimed reveal applications for the protection and control of mastitis and levels of applications in 177 small scale and 169 large-scale farms in Turkey. Materials and Methods: Benefiting from statistical methods analyzed collecting data on udder health of 346 dairy cattle farms in different provinces of Turkey. Results: It has been observed that there are maximum 50-200 cows (n = 96, 56.8% and at most Holstein breeds (n = 97, 57.4%)) in large-scale and 11-20 cows (n = 71, 40.1% and the highest number of Simental breeds (n = 153, 86.4%)) in small scale farms and there are 4 old cows more in these two types of farms. It was determined that the applications of teat dipping (70.4%), dry period antibiotics (72.8%), teat seal (9.5%) and mastitis vaccine (55.6%) in large farms were higher than small scale farms and It was determined that the proportion of those which do predipping and postdipping is higher than those which do not, and that iodine antiseptics are used the most in applications. The rate of those which do not apply milking hygiene in family-type (61.6%) is high. The effects of farms type (p<0.000) and breed (p<0.001) on daily average milk yield in these two types of farms were found to be statistically significant. Conclusion: As a result, the dairy farms in Turkey the proportion of these applications, compared with past years but have been found to be higher than the desired level. © 2021 Eurasian Journal of Veterinary Sciences. All rights reserved.
Turkiye'de farkli niteliklere sahip sut sigiri isletmelerinde mastitisin koruma ve kontrolu kapsamindaki bazi uygulamalarin duzeyleri
Keywords: Cow; Farm; Mastitis; Protection; Turkey